2020
DOI: 10.1111/jvim.15986
|View full text |Cite
|
Sign up to set email alerts
|

Breed predispositions, clinical findings, and prognostic factors for death in dogs with nonregenerative immune‐mediated anemia

Abstract: Background: Breed predispositions, survival, and prognostic factors have not been evaluated in dogs with nonregenerative immune-mediated anemia (nrIMA). Hypothesis/Objectives: To describe clinicopathologic variables, evaluate their associations with survival, and determine breed predispositions for dogs with nrIMA. Animals: Fifty-nine client-owned dogs with nrIMA. Methods: Referral hospital records were reviewed retrospectively for dogs with primary nrIMA (PCV ≤30%, corrected reticulocyte percentage (CR%) ≤1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(61 citation statements)
references
References 22 publications
5
54
2
Order By: Relevance
“…Moreover, the 42 attending clinicians who responded reported that 70% of the DAT+ dogs with IMHA recovered or were clinically stable, while 30% of them died or were euthanized. These findings concur with prior outcome surveys [ 19 , 72 ]. Thus, while the results of the follow-up data are sparse in this as well as in prior studies [ 3 , 24 , 25 , 44 , 69 ], they support the value of monitoring dogs with IMHA during and after treatment.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, the 42 attending clinicians who responded reported that 70% of the DAT+ dogs with IMHA recovered or were clinically stable, while 30% of them died or were euthanized. These findings concur with prior outcome surveys [ 19 , 72 ]. Thus, while the results of the follow-up data are sparse in this as well as in prior studies [ 3 , 24 , 25 , 44 , 69 ], they support the value of monitoring dogs with IMHA during and after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Among the samples tested in this study, dogs with a positive DAT result had more frequent and more severe anemia (Hct < 18%) as was previously described [ 44 , 46 ], and the anemia was more likely regenerative in contrast to those in the DAT- group [ 19 , 25 , 43 ]. While there is no published study to directly compare our observations to, it is likely that some DAT- dogs had non-hemolytic anemias.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations